Race to the top and race to the bottom: Tax competition in rural China - Yao, Yi; Zhang, Xiaobo (International Food Policy Research Institute, 2008)
Fiscal federalism has been argued to intensify regional competition and promote economic growth. This paper is the first, to our knowledge, to empirically assess the patterns and extent of strategic tax competition between geographically neighboring governments in China. Using a panel data set containing data at the county level, we apply Anselin's (1995) local indicator of spatial association (LISA) approach to statistically test the existence of local capital tax competition and examine its determining factors. We find heterogeneous tax competition behaviors across regions. Under decentralized fiscal structure and centralized merit-based governance structure, local governments have strong incentives to compete with each other to attract mobile capital. Counties in the coastal areas with favorable initial conditions of larger tax base tend to race to the bottom" by lowering tax rates so as to create a pro-business environment. In contrast, the local governments in poor regions have difficulty in competing with the governments on the coast to attract investment and develop the local nonfarm economy. Their local revenues are sometimes barely sufficient to cover the salaries of civil servants on the public payroll. Consequently, they are more likely to levy heavy taxes on existing enterprises, worsening the business investment environment. This leads to a ?race to the top? in raising effective tax rate in lagging regions."